HIBP diagnostic for Uragan-2M stellarator - Bondarenko, I.S.; Chmyga, A.A.; Deshko, G.N.; Komarov, A.D.; Kozachok, A.S.; Krupnik, L.I.; Khrebtov, S.M.; Zhezhera, A.I. (Вопросы атомной науки и техники, 2009)
The project of the Heavy Ion Beam Probe (HIBP) plasma diagnostic system for stellarator Uragan-2M is presented. The device Uragan-2M is the flexible torsatron machine with small helical ripples and considerably high size and magnitude of the magnetic field (R = 170 cm, ape = 22 , B0 = 0.8…2.4 T, l = 2, m = 4). Necessary calculations by using the computer code made in HIBP group to optimize HIBP diagnostic set for stellarator Uragan-2M